Alternative Splicing Diversified the Heat Response and Evolutionary Strategy of Conserved Heat Shock Protein 90s in Hexaploid Wheat (Triticum aestivum L.) - Lu, Yunze; Zhao, Peng; Zhang, Aihua; Ma, Lingjian; Xu, Shengbao; Wang, Xiaoming (Frontiers in Genetics, 2020)
Crops are challenged by the increasing high temperature. Heat shock protein 90 (HSP90), a molecular chaperone, plays a critical role in the heat response in plants. However, the evolutionary conservation and divergence of HSP90s homeologs in polyploidy crops are largely unknown. Using the newly released hexaploid wheat reference sequence, we identified 18 TaHSP90s that evenly distributed as homeologous genes among three wheat subgenomes, and were highly conserved in terms of sequence identity and gene structure among homeologs. Intensive time-course transcriptomes showed uniformly expression and transcriptional response profiles among the three TaHSP90 homeologs. Based on the comprehensive isoforms generated by combining full-length single-molecule sequencing and Illumina short read sequencing, 126 isoforms, including 90 newly identified isoforms of TaHSP90s were identified and each TaHSP90 generated one to three major isoforms. Intriguingly, the numbers and the splicing modes of the major isoforms generated by three TaHSP90 homeologs were obviously different. Furthermore, the quantified expression profiles of the major isoforms generated by three TaHSP90 homeologs also distinctly varied, exhibiting differential alternative splicing responses of homeologs. Our results showed that the alternative splicing diversified the heat response of the conserved TaHSP90s and provided a new perspective for understanding about functional conservation and divergence of homologous genes.